The role of Streptococcus pneumoniae in community-acquired pneumonia among adults in Europe: a meta-analysis - Rozenbaum, M. H.; Pechlivanoglou, P.; van der Werf, T. S.; Lo-Ten-Foe, J. R.; Postma, M. J.; Hak, E. (European journal of clinical microbiology & infectious diseases, 2013)
The primary objective of this meta-analysis was to estimate the prevalence of adult community-acquired pneumonia (CAP) caused by Streptococcus pneumoniae in Europe, adjusted for possible independent covariates. Two reviewers conducted a systematic literature search using PubMed on English-language articles that involved human subjects with CAP during the period from January 1990 to November 2011 across European countries. A mixed-effects meta-regression model was developed and populated with 24,410 patients obtained from 77 articles that met the inclusion criteria. The model showed that the observed prevalence of S. pneumoniae in CAP significantly varies between European regions, even after adjusting for explanatory covariates, including patient characteristics, diagnostic tests, antibiotic resistance, and health-care setting. The probability of detecting S. pneumoniae was substantially higher in studies that performed more frequently a diagnostic polymerase chain reaction assay compared to all the other diagnostic tests included. Furthermore, S. pneumoniae was more likely to be confirmed as the cause of a CAP in studies with intensive care unit patients as compared to those with hospital- or community-treated patients. This study provides estimates of the average observed prevalence of S. pneumoniae , which could be used for projecting the health and economic benefits of pneumococcal immunization.